LEGAL REVIEW OF FOREST CONVERSION FOR PALM OIL PLANTATIONS IN THE INTERESTS OF RENEWABLE ENERGY - Evy Harjono (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Abstract Forest conversion for oil palm plantations is a complex issue in Indonesia. This sector contributes significantly to the national economy through exports and job creation, but on the other hand causes negative impacts such as deforestation, loss of biodiversity, and agrarian conflicts involving indigenous peoples and small farmers. The government has established various regulations, including Law No. 41 of 1999 concerning Forestry, Law No. 32 of 2009 concerning Environmental Protection and Management, and Law No. 39 of 2014 concerning Plantations to control forest conversion. Unfortunately, the implementation of this policy still faces challenges, especially in terms of law enforcement and licensing transparency. This study uses a normative juridical method by analyzing national regulations and international policies such as the 2015 Paris Agreement and the Convention on Biological Diversity (CBD). The results of the study show that weak supervision, corruption in licensing, and minimal coordination between agencies are the main obstacles in managing forest conversion. Therefore, a stricter strategy is needed in monitoring licensing, increasing transparency in land management, and implementing stricter sanctions for violators of regulations. In addition, sustainability standards such as the Roundtable on Sustainable Palm Oil (RSPO) and Indonesian Sustainable Palm Oil (ISPO) need to be strengthened to ensure that the palm oil industry can develop without damaging the environment. With these steps, it is hoped that the management of natural resources in Indonesia can be more balanced between economic, social, and ecological interests.